Unresectable Recurrent Squamous Cell Carcinoma of the Temporal Bone Treated by Induction Chemotherapy Followed by Concurrent Chemo-Reirradiation. Issue 9 (October 2015) - Kun, Ma; Xinxin, Zhang; Feifan, Zhao; Lin, Ma
<x xml:space="preserve">Abstract</x> Objective: To report a rare case of recurrent temporal bone carcinoma encasing the carotid artery. Patient: A 54-year-old man underwent mastoidectomy combined with adjuvant chemoradiotherapy of squamous cell carcinoma of the temporal bone. He developed metastatic disease and received parotidectomy and lymph node dissection. Three months later, the magnetic resonance imaging scan showed that the tumor had relapsed and invaded the carotid artery. Intervention: The patient completed TPF-C induction chemotherapy (docetaxel, cisplatin, 5-fluorouracil, cetuximab), followed by concurrent chemotherapy with reirradiation. Results: Magnetic resonance imaging revealed a complete response of tumor 1 month after treatment. The patient had no detectable recurrence after 53 months of follow-up. Conclusion: Concurrent chemotherapy with reirradiation is a potential curative treatment option for patients who have unresectable recurrent squamous cell carcinoma of the temporal bone.